Long lasting insecticidal mosquito nets (LLINs) ownership, use and coverage following mass distribution campaign in Lake Victoria basin, Western Kenya - Peter N. Ng'ang'a; Polycarp Aduogo; Clifford M. Mutero (BMC, 2021)
Abstract Background Long-lasting insecticidal nets (LLINs) are the most widely used malaria prevention and control intervention in Africa. However, their effectiveness may vary depending on their local geographic coverage, ownership and use at household level. This study aimed at assessing LLINs ownership and use following mass distribution campaign in western Kenya. Methods A cross-sectional study was conducted in November 2017. A total of 160 households were randomly selected from 16 villages. Structured questionnaires were used to collect data on households' knowledge on malaria, LLINs ownership, utilization and their perceived benefits. Data was analyzed using IBM Statistical Package for Social Sciences (SPSS) version 21 for windows. Variables were presented as proportions and associations between variables tested using Pearson's chi-square test. Results Malaria was reported to be the most frequently occurring disease (87.5%) in the area. Children under 5 years of age were reported to be at higher risks of malaria infection (28.6%). Around 31% of the respondents reported to have at least one member of the household sick with malaria a week before the interview. Commonly cited signs and symptoms of malaria were; fever (24.1%), headache (17.7%), vomiting (14.5%) feeling cold (12.6%) and loss of appetite (10%). There were 382 reported LLINs among 753 occupants in the 160 households surveyed. The average LLIN ownership was 2.4 nets per household and 1.97 persons per LLIN. Among the surveyed households, 96.9% owned at least one LLIN and 64.1% owned at least one LLIN for every two people. Among those who owned LLINs, 98.1% reported using them the previous night. Ownership per household ranged from 0 to 6 with a mean of 2.39. More than three quarter of the nets were acquired through free mass distribution campaigns and 80% were acquired less than 6 months prior to the survey. Conclusion Despite high net coverage and use, a number of households experienced malaria episodes in the study area. There is need to investigate the likelihood of outdoor malaria transmission and assess the physical integrity of the existing LLINs and their insecticidal effectiveness in protecting household members against malaria.